Paradigma Penentuan Awal Waktu Subuh: Tinjauan Fikih dan Ilmu Falak - Akbar, Reza; Djamaluddin, Thomas; Izzuddin, Ahmad; Nurkhanif, Muhammad (AL-SULTHANIYAH, 2025)
Determining the Beginning of Fajr Time is an important issue that requires synergy between scientific and shar‘i approaches. The fajr ṣādiq (true dawn) as the indicator marking the beginning of Fajr time has become the main focus of various astronomical studies and fiqh discussions. However, the criteria for determining Fajr time remain a matter of debate to this day. This study employs a qualitative-descriptive approach through library research to reconstruct the paradigm of dawn observation based on the integration of astronomy (‘ilm al-falak) and Islamic jurisprudence (fiqh). The findings show that the paradigm for determining the beginning of Fajr time is grounded in identifying the earliest, most accurate, and objective appearance of the fajr ṣādiq. The analogical approach to determining the beginning of the Hijri month reinforces the scientific principle of dawn observation, namely the use of the lowest threshold criterion in identifying the first astronomical phenomenon that signifies a change in time. The application of this principle, as adopted by LF PBNU, reflects a shared paradigm between science and fiqh in affirming the boundaries of worship times both empirically and normatively.